Simulated Microgravity Induces the Proliferative Inhibition and Morphological Changes in Porcine Granulosa Cells - Truong Xuan Dai; Hoang Nghia Son; Ho Nguyen Quynh Chi; Hoang Nghia Quang Huy; Nguyen Thai Minh; Nguyen Thi Thuy Tram; Nguyen Thi Thuong Huyen; To Minh Quan; Doan Chinh Chung; Truong Hai Nhung; Tran Thi Minh; Tran Hong Diem; et al. (Current Issues in Molecular Biology, 2021)
Astronauts are always faced with serious health problems during prolonged spaceflights. Previous studies have shown that weightlessness significantly affects the physiological function of female astronauts, including a change in reproductive hormones and ovarian cells, such as granulosa and theca cells. However, the effects of microgravity on these cells have not been well characterized, especially in granulosa cells. This study aimed to investigate the effects of simulated microgravity (SMG) on the proliferation and morphology of porcine granulosa cells (pGCs). pGC proliferation from the SMG group was inhibited, demonstrated by the reduced O.D. value and cell density in the WST-1 assay and cell number counting. SMG-induced pGCs exhibited an increased ratio of cells in the G0/G1 phase and a decreased ratio of cells in the S and G2/M phase. Western blot analysis indicated a down-regulation of cyclin D1, cyclin-dependent kinase 4 (cdk4), and cyclin-dependent kinase 6 (cdk6), leading to the prevention of the G1-S transition and inducing the arrest phase. pGCs under the SMG condition showed an increase in nuclear area. This caused a reduction in nuclear shape value in pGCs under the SMG condition. SMG-induced pGCs exhibited different morphologies, including fibroblast-like shape, rhomboid shape, and pebble-like shape. These results revealed that SMG inhibited proliferation and induced morphological changes in pGCs.